Pemanfaatan Media Pembelajaran Buku Cerita Bergambar dalam Meningkatkan Minat Baca Siswa SD (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This research aims to explore the use of picture story books in increasing elementary school students' reading interest. The method used is a literature review which involves collecting and analyzing various academic sources related to interest in reading, picture story books, and the effectiveness of learning media. The research results show that picture story books have significant benefits, such as increasing the attractiveness of reading, facilitating understanding, and increasing students' emotional involvement. Not only that, strategies such as interactive reading, discussions and creative activities have proven effective in maximizing the use of picture story books. Even though there are challenges such as limited access to quality books and minimal training for teachers, collaborative efforts between schools, government and parents are needed to improve the culture of literacy among children.